KOMPETENSI PROFESIONAL GURU BIMBINGAN DAN KONSELING DI MADRASAH ALIYAH - Khaldun, Rendra (Jurusan Bimbingan dan Konseling Islam Fakultas Dakwah dan Komunikasi IAIN Mataram, 2016)
The implementation of guidance and counseling in Indonesia started from educational settings since 1960s, as a form of government awareness in responding the educational problem and as an acceleration step in improving and increasing human resources. The seriousness of the government in optimizing the role of educational counselor, it is appeared clearly by expanding the counselorâs space and regulating the profession in legislation and government regulations. The role of counselor become more prosperous in educational institution, marked by counselor mandate to apply counseling service listed in the curriculum of 2013. On the other hand, the existence of counselors in educational settings characterized by the appearance of national education system 2003 article 1 paragraph 6 and Government Regulation of the Republic of Indonesia number 74 in 2008 about teacher article 54 item 6, mentioned that âthe workload of the guidance teacher and counseling or counselor who obtain professions allowances andÂ additional allowance educate at least 150 students per year on one or more educational level. By observing the governmentâs seriousness in expressing the existence of the counselor in educational institution, it should be followed by preparing the competence of professional expert in handling the expert service for the learners. . The aspects contained in the competence including knowledge, understanding, skill, attitude, interest, value, and sensitive, toward the development of knowledge, the improvement of those competences in improving performance in order to give satisfaction in fulfilling the needs of the learners.